AutoCAD 2011 and AutoCAD LT 2011 no experience required - Gladfelter, Donnie 1982- (Autodesk official training guide, 2010)
"A step-by-step tutorial on AutoCAD and AutoCAD LT basics. AutoCAD is the leading drawing software, used by design and drafting professionals to create 2D and 3D technical drawings. This tutorial is aimed at AutoCAD novices and provides you with the essentials you need so you can acquire the necessary skills to work in AutoCAD and AutoCAD LT immediately. You'll begin with the basics and gradually progress to more advanced topics and features, such as grouping, elevations, hatches, and using text in drawings. Concise explanations, focused examples, and step-by-step instructions round out this hands-on tutorial. Begins with the basics of AutoCAD and AutoCAD LT, the leading 2D and 3D drawing software. Progresses to more advanced topics and skill sets and covers grouping, hatches, and text in drawings. Introduces dimensioning, external references, layouts and printing, and using 3D Contains helpful examples and step-by-step instructions so you can get started using AutoCAD immediately. Featuring the most up-to-date techniques, tactics, industry standards, and methods, this tutorial will get you started using AutoCAD and AutoCAD LT right away."